Post-healing perceptions and experiences of alcohol withdrawal and life management in men with alcoholic pancreatitis: a qualitative study - Chen, Runpeng; Wang, Qinghua; Wang, Dongyang; Liu, Xinyue; Wang, Haiyun; Guo, Jiaoyang; Liu, Xinghui (Frontiers in Psychology, 2023)
Introduction The aim of this study was to examine the perceptions and experiences of male patients with alcoholic pancreatitis after healing regarding alcohol withdrawal and life management. Methods This study used a qualitative descriptive design, and participants were selected by purposive sampling from two tertiary care hospitals in Shandong Province, China. Semi-structured in-depth interviews were conducted with 18 male patients discharged from the gastroenterology department who had recovered from alcoholic pancreatitis. Colaizzi’s method was used to analyze the interview data, and the findings were reported using COREQ criteria. Results By analyzing the interview data, we summarized five themes, (1) the dilemma of sobriety, (2) role change, (3) illness status, (4) family influence, and (5) life management. Conclusion By profiling the perceptions and experiences of post-healing alcoholic pancreatitis patients’ alcohol cessation and life management in men, it helps to grasp the details of alcohol cessation and health direction of patients’ home management, which provides more directional guidance to help patients maintain positive and good lifestyle habits and active management awareness, followed by targeted personalized interventions to provide patients with knowledge of disease care and health management.